IMPLEMENTASI DESAIN INFORMASI VISUAL MELALUI INSTAGRAM MENGGUNAKAN METODE MDLC: IMPLEMENTATION OF VISUAL INFORMATION DESIGN VIA INSTAGRAM USING THE MDLC METHOD - Sri Mulyani; Alif Budi Santoso; Hersatoto Listiyono (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
The National Search and Rescue Agency, known as BASARNAS, in carrying out its main tasks and functions in the field of search and rescue (SAR) requires information media with a wide reach so that more people or the public will feel the impact and benefits. This research focuses more on the implementation of easier and more attractive information designs for the public that can be accessed through Instagram social media. The information design presented visually using the MDLC method developed by Luther Sutopo is expected to be able to answer the challenges faced by BASARNAS Semarang in terms of disseminating information related to tasks, activities and events to the wider community. In this research activity, testing was carried out by distributing questionnaires to 100 respondents to explore responses to the information design that had been uploaded to Instagram. The results reveal that the overall visual design of the information presented is attractive and easy to understand. The colors used are contrasting, and the BASARNAS Logo is easy to find in the design.